Analysis of Students' Problem-Solving Skill in Learning Mathematics at State Elementary School 1 Sukorejo - Putri, Tania Diar Kristian; Suryandari, Kartika Chrysti; Yulisetiani, Septi (Universitas Sebelas Maret, 2026)
Current education demands students to have the ability to solve problems or problem-solving during learning activities, especially in certain subjects such as mathematics. This study aims to determine the results of the initial problem-solving abilities of 6th grade students in mathematics at SD Negeri 1 Sukorejo. This research method uses quantitative descriptive. Data collection was carried out through interviews with homeroom teachers, observations of students and teachers during learning activities, and questionnaires for students. Respondents in this study were homeroom teachers and 6th grade students. The results of data analysis obtained from interviews with homeroom teachers indicate that the mathematics learning process is not always optimal due to the lack of learning tools that can support students' problem-solving abilities. This is supported by the results of observations of learning activities in the classroom, which show that teachers have not yet maximized varied learning models to improve the problem-solving abilities of 6th grade students. The results of the questionnaire on students' problem-solving abilities also show that many are still in the low category in several aspects such as solution determination, implementation, and reflection evaluation. Based on the results of the data obtained, it can be concluded that the problem-solving abilities of 6th grade students at SD Negeri 1 Sukorejo in mathematics are still low.